2020
DOI: 10.1016/s2214-109x(20)30155-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, acceptability, and design of a mobile health application for high-risk men who have sex with men in Hanoi, Vietnam

Abstract: Background Approximately three quarters of men who have sex with men (MSM) in Vietnam have used a phone or tablet to search for sexual health information online, and over half of these men have used it to locate nearby service providers. As HIV prevalence continues to rise in Vietnamese MSM, smartphones and other electronic media may provide an ideal platform for HIV research and intervention. Here, we describe a pilot study of an ecological momentary assessment (EMA) application (app) and a wearable device (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Many product orientation papers published from 2016 to date have examined the practicality, usefulness, and feasibility of some mHealth applications in various fields such as HIV, maternal and infant health, sexual and reproductive health and user satisfaction and acceptance. [31][32][33][34][35] Furthermore, several market-orientation investigations have been conducted. Using a quantitative approach, studies have found that there is a low percentage of mHealth application users; however, the younger generations were mostly satisfied with mHealth innovations that they had experienced and were ready, and felt receptive to more useful mHealth applications in the near future.…”
Section: The Roles Of Mhealth In Mitigating the Covid-19 Pandemic In The Developing Countriesmentioning
confidence: 99%
“…Many product orientation papers published from 2016 to date have examined the practicality, usefulness, and feasibility of some mHealth applications in various fields such as HIV, maternal and infant health, sexual and reproductive health and user satisfaction and acceptance. [31][32][33][34][35] Furthermore, several market-orientation investigations have been conducted. Using a quantitative approach, studies have found that there is a low percentage of mHealth application users; however, the younger generations were mostly satisfied with mHealth innovations that they had experienced and were ready, and felt receptive to more useful mHealth applications in the near future.…”
Section: The Roles Of Mhealth In Mitigating the Covid-19 Pandemic In The Developing Countriesmentioning
confidence: 99%
“…Overall, study participants had positive feedback about their experience citing preferences for a more tailored experience (i.e., providing feedback on mood and behavior, MSM-friendly messaging) in the future. Additionally, participants stated the ability for telemedicine and locations of HIV service providers nearby as desirable features for future apps [ 56 ]. However, a limiting factor of using data from EMA’s and other apps is that they would require typically individuals to download the app.…”
Section: Wearable Devices Apps and Sensorsmentioning
confidence: 99%
“…mHealth interventions have shown promising results in improving medication adherence [24,25], health care engagement [24,26,27], and other health-promoting behaviors such as engagement in physical activity [28][29][30] in diverse populations. Furthermore, mHealth may be an acceptable and feasible approach for delivering care, including mental health care, to MSM both in high-income countries and low-and middle-income countries (LMICs), including Malaysia, China, India, Thailand, and Vietnam [31][32][33][34][35][36][37][38][39][40]. This is because MSM are often early adopters of technology and may already use such platforms to access health information and search for sexual partners [34,41].…”
Section: Introductionmentioning
confidence: 99%